Association of 5-HTTLPR Polymorphism with the Nursing Diagnoses and the Achievement of Nursing Outcomes in Patients with Major Depression. (3rd October 2017) - Prokofieva, Margarita; Karadima, Georgia; Koukia, Evmorfia; Michou, Vassiliki; Kyprianidou, Chrysoula; Papageorgiou, Chrysovalantis V.; Alexiadis, Evangelos; Constantoulakis, Pantelis; Dikeos, Dimitris
ABSTRACT: The aim of this study is to investigate whether a 44-base-pair insertion/deletion polymorphism in the upstream regulatory region of the serotonin transporter gene (5-HTTLPR) is associated with the nursing diagnoses and the achievement of the desired nursing outcomes in inpatients with major depression. Thirty five patients were evaluated. The nursing diagnoses of risk for suicide and imbalanced nutrition are reported less often in homozygotes of the high-expressing gene (LA ). Carriers of the low-expressing genes (LG or S) have a worse response to interventions which aim to increase low self-esteem, indicating that they may need more intensive care in order to achieve the desired outcome. Genetics in psychiatric nursing could help refine personalized care, however further studies with large sample sizes and multiple gene evaluations are needed.